English Teachers’ Perception on the Use of Authentic Assessment in 2013 Curriculum - Mardjuki, Moch. Said (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Authentic assessment in 2013 Curriculum leads the students to be autonomous learner and become higher order thinking. However, the English teachers prefer to use non-authentic than authentic assessment. This study seeks to find out how English teachers use the authentic assessment in the classroom and the barriers and the way the English teachers solve the problems in conducting authentic assessment. Interview was used to find out of five postgraduate English education students at a university in Bandung used authentic assessment in the classroom. Authentic assessment can encourage the English teachers and students to be more creative and optimize student’s participation in learning process. However, several challenges lead to the implementation of authentic assessment: purpose of assessment, fairness, time allotment, objectivity and reliability of scoring. Therefore, 2013 Curriculum should be clearly stated the types of authentic assessment, the indicators, and time allocation to its teaching material.